2022
DOI: 10.3390/jpm12010104
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Pharmacogenomics and Personalized Medicine in the United Arab Emirates

Abstract: The application of personalized medicine (PM) is rapidly evolving [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Therefore, knowledge and educational background about PGx becomes more crucial as the demand towards PGx and personalized medicine in the UAE is becoming more noticeable. 50 Recently, a focus group discussion was conducted on pharmacists working in the UAE. The study outcome recommended several key factors that were concluded from the discussion with the pharmacists.…”
Section: Knowledge and Attitudes Of Physicians And Pharmacists Toward...mentioning
confidence: 99%
“…Therefore, knowledge and educational background about PGx becomes more crucial as the demand towards PGx and personalized medicine in the UAE is becoming more noticeable. 50 Recently, a focus group discussion was conducted on pharmacists working in the UAE. The study outcome recommended several key factors that were concluded from the discussion with the pharmacists.…”
Section: Knowledge and Attitudes Of Physicians And Pharmacists Toward...mentioning
confidence: 99%
“…Several factors have been implicated in justifying this practical resistance [ 18 ]. These include knowledge lagging behind a positive attitude for practice by healthcare professionals, high cost, lack of standardized guidelines, and the yet-to-be addressed ethical and social implications [ 11 , 19 , 20 ]. For instance, CPIC explicitly states that its published guidelines are only designed to help practitioners “understand how available genetic test results should be used to optimize drug therapy, rather than whether the tests should be ordered.” [ 21 ].…”
Section: Introductionmentioning
confidence: 99%